1982
DOI: 10.1111/j.1365-2389.1982.tb01799.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pH upon the copper and cupric ion concentrations in soil solutions

Abstract: Soil samples whose pH had been adjusted to between 4.5 and 7.5 either for long periods in the field or short periods in the laboratory were incubated after wetting with water or 0.01 M CaCl2. Copper concentrations in the soil solutions decreased only slightly as the solution pH increased, but free cupric ion concentrations decreased considerably. The copper concentrations were smaller and the proportion of copper present in solution as cupric ion at a given pH was larger when CaCl2 rather than water was used. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
2
2

Year Published

1985
1985
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(39 citation statements)
references
References 15 publications
2
33
2
2
Order By: Relevance
“…These results indicate a high Cu adsorption capacity of the soils and are in agreement with Msaky & Calvet (1990) that observed complete adsorption of the Cu added to soil, even at low pH. On the other hand, the elevation of soil pH above 5.0 resulted in decrease of Cu concentration in solution (Sanders, 1982), which indicates the influence of higher pH values on the Cu sorption to the soil. The metals with higher electronegativities form stronger covalent & Crawford, 1973a;Shuman, 1985;Sims, 1986).…”
Section: Resultssupporting
confidence: 90%
“…These results indicate a high Cu adsorption capacity of the soils and are in agreement with Msaky & Calvet (1990) that observed complete adsorption of the Cu added to soil, even at low pH. On the other hand, the elevation of soil pH above 5.0 resulted in decrease of Cu concentration in solution (Sanders, 1982), which indicates the influence of higher pH values on the Cu sorption to the soil. The metals with higher electronegativities form stronger covalent & Crawford, 1973a;Shuman, 1985;Sims, 1986).…”
Section: Resultssupporting
confidence: 90%
“…Estimating the level of soluble Ca2+ at about 10-3 M and assuming that all soil Cu 2 + is exchangeable, one would estimate a Cu 2 + solubility in these soils to be about 10-5 M from equation 2. The much lower solubilities obtained in reality (Sanders, 1982) lead to the obvious conclusion that mechanisms much more specific than ion exchange are needed to explain the behavior of Cu and other heavy metals. In fact, evidence for specific adsorption of metals such as C02+, Zn 2 +, and Cd2+ (Hodgson, 1960;Tiller and Hodgson, 1962;Page, 1976, 1977) has been obtained for very low adsorption levels on layer silicate clays.…”
Section: Ion Exchange On Layer Silicatesmentioning
confidence: 88%
“…Soil pH is the most widely accepted parameter which exerts a controlling influence on the availability of micro-nutrients and heavy metals in the soil to plants (Sanders, 1982;Igwe et al, 2005). Banjoko and Sobulo, (1994) reported that some Nigerian soils especially in the forest and savannah regions are within a pH range of 5.70 -6.50.…”
Section: Resultsmentioning
confidence: 99%